Cu(OTf)2/NBS Promoted Cyclization of 1‐Cinnamyl Alcohol‐o‐Carboranes: An Efficient Approach for Synthesis of o‐Carboranes Substituted Oxetanes. Issue 2 (22nd December 2022) - Zhang, Cai‐Yan; Cao, Ke; Yang, Han‐Bo; Jiang, Linhai; Li, Bo; Yang, Junxiao
Abstract: The Cu(OTf)2 /NBS promoted cyclization of 1‐cinnamyl alcohol‐ o ‐carboranes for synthesis of o ‐carborane substituted oxetanes has been developed. A series of substituted oxetanes has been synthesized with moderate to good yields, which would be an important synthon for design novel reactions in oxetane chemistry as well as carborane chemistry. Abstract : Cu(OTf)2 /NBS promoted cyclization of 1‐cinnamyl alcohol‐ o ‐carboranes offers a novel synthon of o ‐carborane substituted oxetane.